PERAN INDONESIA-JAPAN COAL POLICY DIALOGUE (IJCPD) TERHADAP PENGEMBANGAN BATUBARA INDONESIA - Andre Tandiawan; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This Research is about cooperation between two countries in energy security sector, that provides an analyze of the role Indonesia-Japan Coal Policy Dialogue (IJCPD), in maintaining the future of Indonesia’s coal energy resources, there are 3 aspects , technology, human resources and domestic obligation/coal trading. Energy security become an issue that affect not only in big country, but also in developing country especially Indonesia. High intensity energy resources, certainly very important for industrialization and development country. Indonesia have so many coal energy potentials, and until now Indonesia’s still depend on petroleum energy that keep decrease every years. Indonesia has looking for diversification energy that compromise for energy security in the future, it can replace petroleum as main energy sector in Indonesia, and coal is an answer for Indonesia to maintain energy security in the future.In this research use the conceptual basis, with the concept of the role Indonesia-Japan Coal Policy Dialogue (IJCPD) as a forum cooperation between two countries that focusing on development energy security especially in coal energy resources. Backed by the Theory of International policy, The concept leads to qualitative methods , field research and also library research for references.Some of the role performs of Indonesia-Japan Coal Policy Dialogue (IJCPD) to become a cooperation dialogue between two countries and joint development to strengthen countries relation and maximize each countries especially in coal energy sector.Keywords: Energy Security, Indonesia, Indonesia-Japan Coal Policy Dialogue (IJCPD), Role, Coal